Synchronous and Asynchronous Communication in Teaching English (Journal of Pedagogical Inventions and Practices, 2023)
The article analyzes the possibilities and features of the implementation of the process of short-term training courses on teaching English in distance education in online (synchronous) and offline (asynchronous) forms